Wanting "Something More": A Review of Marriage and Meaning in Dollahite, Hawkins, and Parr (2012). Issue 4 (18th May 2016) - Dwyer, Adria J.; Chauveron, Lisa M.
Abstract : In "Something More": The Meanings of Marriage for Religious Couples in America, Dollahite, Hawkins and Parr (2012) present a qualitative study that includes interviews with religiously observant married couples to investigate marriage. The current paper reviews the aforementioned study with respect to its trustworthiness, through dependability, credibility, confirmability and transferability, to encourage the elevation of qualitative work in our field. We discuss a number of challenges in the study design, methods, interpretation, and conclusions. In sum, our reading of the study left us wanting "something more" scholarly rigorous for the field of marriage research and qualitative work.